Rapid and Elevated Tumor Responses to Wekley Paclitaxel for AIDS-Related Kaposi Sarcoma - Berrad, S.; Oualla, K.; Lokonga, V. W.; Nouiakh, L.; H. Erraichi; L. Amaadour; Z. Benbrahim; S. Arifi; N. Mellas (International Journal of Innovative Research in Medical Science, 2020)
Kaposi sarcoma is a rare condition, it is an incurable disease with a poor prognosis, the treatment of this pathology is variable including surgery, Radiotherapy, chemotherapy and antiviral treatments. A number of drugs approved for the treatment of KS associated with AIDS, in particular the pegylated liposomal doxorubicin (DLP) which is currently the standard, Paclitaxel, have also shown efficacy against advanced SK. We report a case of a patient with kaposi's sarcoma associated with HIV metastatic in the lung, liver and lymph nodes and who presented an almost complete response after 4 months of chemotherapy with weekly Paclitaxel at a dose of 100 mg in our department of medical oncology at CHU Hassan II in Fez. Of interest is the complete response to paclitaxel treatment in a patient followed for metastatic kaposi sarcoma.